Sejarah Peradaban Islam di Pulau Madura - Alfiandi Zikra; M. Iqbal Irham; Sugeng Wanto (Journal on Education, 2023)
In the book Negarakertagama which was written by Mpu Prapanca when under the rule of King Hayamwuruk from the Majapahit kingdom in 1365 AD, initially Madura was an archipelago with Java. Some argue that the islands of Madura and Java were separated in 929 AD due to a volcanic eruption. Islam entered Madura intensively around the 15th century AD along with the waning influence of the Majapahit kingdom in East Java. In the 16th century Madura was divided into two regions. first, west madura whose area is Arosbaya which later became Bangkalan and Sampang. The two East Madura, namely Sumenep and Pamekasan. The history of the development of Islam in Bangkalan began with the reign of Panembahan Pratanu, who had the title Weak Dhuwur. While the spreaders of Islam in Sumenep include Sunan Padusa. The spread of Islam on the island of Madura was spread through trade, not by war. This is in accordance with the Islamic religious principle of spreading peace. The war that occurs is only to maintain what already exists, not to hold something that doesn't yet exist.